Vienna. Great Hall of the National Library; Vienna. Schönbrunn Castle, the Great Gallery (Berlin; Ernst Wasmuth, 2020)
Photogravure of the interiors of the Nationalbibliothek and the gallery at Schönbrunn Palace in Vienna